1982
DOI: 10.1002/bem.2250030402
|View full text |Cite
|
Sign up to set email alerts
|

The vacuolar potential of characean cells subjected to electromagnetic radiation in the range 200–8,200 MHz

Abstract: Single giant cells of Chara braunii and Nitella flexilis were placed in a microstrip exposure apparatus and subjected to bursts of electromagnetic radiation (carrier frequencies from 200 to 8,200 MHz) at a nominal power level of 100 W/m2. The vacuolar potential was monitored with a micropipette, and offsets as low as 1 microV could be resolved in real time by suitable filtering and signal averaging; under these conditions, no offsets of the vacuolar potential were detected. At much higher power levels (corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…These results seem to suggest a direct microwave field interaction with nerve cells, since the saline temperature was held constant [Arber, 1976[Arber, , 1981Campbell and Brandt, 19811 and the effect was in opposition to that observed under conventional heating [Wachtel et al, 19751. It should be added that recently Barsoum and Pickard [1982] also found a fall in the membrane resistance of Characean cells when temperature of the bathing solution was kept constant. It has been supposed [Arber, 19791 that temperature can influence the conditions under which microwave fields interact with biological objects.…”
Section: Introductionmentioning
confidence: 99%
“…These results seem to suggest a direct microwave field interaction with nerve cells, since the saline temperature was held constant [Arber, 1976[Arber, , 1981Campbell and Brandt, 19811 and the effect was in opposition to that observed under conventional heating [Wachtel et al, 19751. It should be added that recently Barsoum and Pickard [1982] also found a fall in the membrane resistance of Characean cells when temperature of the bathing solution was kept constant. It has been supposed [Arber, 19791 that temperature can influence the conditions under which microwave fields interact with biological objects.…”
Section: Introductionmentioning
confidence: 99%
“…This will provide information on effects of chronic long-term exposure on cardiac cell membranes. Long-term effects have already been reported for frog sciatic nerve [371, snail neurons [2], and plant cells [7].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Those associated with heating lead to perturbation in biological reactions, reaction rates current flow and e ruction of cell membranes (9,10,11,12), thereby producing some observable and measureable physiological parameters. Some studies have shown that exposure to (MW) radiation produced effects which include activation of peritoneal macrophages to a viricidal state (12), increased immune response (13), modification of the lipid peroxidation conditions (14,15). In some of our previous reports) (14,15), we have suggested that many of these effects are caused by free oxygen, free radicals, peroxides and superoxides.…”
Section: Introductionmentioning
confidence: 99%